2018
DOI: 10.1257/aer.20161151
|View full text |Cite
|
Sign up to set email alerts
|

From Final Goods to Inputs: The Protectionist Effect of Rules of Origin

Abstract: Recent decades have witnessed a surge of trade in intermediate goods and a proliferation of free trade agreements (FTAs). FTAs use rules of origin (RoO) to distinguish goods originating from member countries from those originating from third countries. We focus on the North American Free Trade Agreement (NAFTA), the world’s largest FTA, and construct a unique dataset that allows us to map the input-output linkages in its RoO. Exploiting cross-product and cross-country variation in treatment over time, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
121
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 37 publications
1
121
0
1
Order By: Relevance
“…The World Bank (WB), the International Monetary Fund and the World Trade Organization (WTO) recently released a joint report (2017) warning against a turn of the global trade policy agenda. Indeed, in a context of erratic global trade developments, policy issues have returned to the spotlight, both in politics and academia (Feng et al 2017, Murina and Nicita 2017, Baccini et al 2018, Blanchard et al 2016, Conconi et al 2016, Haaland and Venables 2016, Baldwin 2011, Antras and Yeaple 2013, Vandenbussche and Zanardi 2010. Even as tariffs are at historically low levels, non-tariff measures (NTMs) play an important-and growing-role in global trade policy, exemplified by the burgeoning interest of international governmental and non-governmental bodies (i.a., Cadot and Malouche 2012, UN 2013, GTA 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The World Bank (WB), the International Monetary Fund and the World Trade Organization (WTO) recently released a joint report (2017) warning against a turn of the global trade policy agenda. Indeed, in a context of erratic global trade developments, policy issues have returned to the spotlight, both in politics and academia (Feng et al 2017, Murina and Nicita 2017, Baccini et al 2018, Blanchard et al 2016, Conconi et al 2016, Haaland and Venables 2016, Baldwin 2011, Antras and Yeaple 2013, Vandenbussche and Zanardi 2010. Even as tariffs are at historically low levels, non-tariff measures (NTMs) play an important-and growing-role in global trade policy, exemplified by the burgeoning interest of international governmental and non-governmental bodies (i.a., Cadot and Malouche 2012, UN 2013, GTA 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study how trade policies affect firms' export-platform FDI and international sourcing decisions. Related to this issue, Conconi et al (2016) Notes: Heteroscedasticity-consistent standard errors clustered at the affiliate level are in parentheses. The constant term is not reported.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent research shows that tariff preferences have a negative impact on imports from nonmember countries (e.g. Romalis, 2007;Fugazza and Nicita, 2013;Dai, Yotov, and Zylkin, 2014;Limão, 2016), especially if these preferences are coupled with strict rules of origin (Conconi, García-Santana, Puccio, and Venturini, 2018). 5 It has been shown that tariff erosion can be a factor behind the multiplication of RTAs (Baldwin and Jaimovich, 2012;Chen and Joshi, 2010).…”
Section: Introductionmentioning
confidence: 99%